The Effect of Toulmin’s Model of Argumentation Within TWPS Strategy on Students’ Critical Thinking on Argumentative Essay - Eko Suhartoyo; Nur Mukminatien; Ekaning Dewanti Laksmi (Jurnal Pendidikan Humaniora, 2015)
Abstract: This research aimed at investigating the effectiveness of Toulmin’s model of argumentation within TWPS strategy on undergraduate students’ critical thinking on argumentative essay. A quasi-experimental design with a pretest-posttest and nonrandomized control group design was used. The subjects were 38 fourth semester students in English Department of Universitas Negeri Malang.The experimental group was treated by using Toulmin’s model of argumentation within TWPS strategy while the control group was treated without TWPS strategy. Students’ critical thinking ability was measured by using argumentative essay test. ANCOVA was used to test the hypotheses. Findings showed there was not significant difference on the students’ critical thinking ability. However, Toulmin’s model of argumentation within TWPS strategy proved to improve the students’ critical thinking as shown by the improvement of the experimental group’s mean score.   Key Words: critical thinking, Toulmin’s model of argumentation, argumentative essay, Think-Write-Pair-Share strategyAbstrak: Penelitian ini bertujuan untuk menyelidiki efektivitas model argumentasi Toulmin dalam strategi TWPS pada kemampuan berpikir kritis esai argumentative mahasiswa. Desain kuasi-eksperi-mental digunakan dengan pretest-posttest dan nonrandomized control group. Subjek dari penelitian ini adalah 38 mahasiswa semester IV di Jurusan Bahasa Inggris Universitas Negeri Malang. Kelompok eksperimen diteliti dengan menggunakan model argumentasi dalam strategi TWPS sedangkan kelom-pok kontrol diteliti tanpa strategi TWPS. Kemampuan berpikir kritis siswa diukur dengan menggunakan uji esai argumentatif. ANCOVA digunakan untuk menguji hipotesis. Temuan menunjukkan tidak ada perbedaan yang signifikan pada kemampuan berpikir kritis siswa. Namun, model argumentasi Toulmin dalam strategi TWPS terbukti meningkatkan berpikir kritis siswa seperti yang ditunjukkan oleh nilai rata-rata. Kata kunci: berpikir kritis, model argumentasi toulmin, esai argumentatif, Think-Pair-Share Write- strategy